Effect of simultaneous saccharification and fermentation conditions of native triticale starch on the dynamics and efficiency of process and composition of the distillates obtained. Issue 4 (4th July 2012) - Balcerek, Maria; Pielech‐Przybylska, Katarzyna
Abstract BACKGROUND: Among ethanol production technologies, attention should be focused towards simultaneous saccharification and fermentation of native starch with enzymes capable of its degradation without prior gelatinization. Selection of process conditions makes it possible to achieve high efficiency of the process and to reduce the costs of the production of ethanol. RESULTS: This study determined the effect of hydrolysis conditions of native triticale starch based on the results of their fermentation and concentration of by‐products in the distillates obtained. The pre‐activation of starch with acid α‐amylase is not necessary for the proper conduct and efficiency of saccharification and fermentation of native triticale starch. Beneficial impact on the synthesis of ethanol was afforded by the treatment of mashes with protease preparation (EC 3.4.21.62) (Bacillus licheniformis). Raising the pH of mashes from 3.6 to 4.8 did not improve the ethanol yield. Process conditions had a diversified impact on concentration of by‐products in the raw spirits obtained. CONCLUSION: Under the optimal conditions found in these experiments 63.01 ± 0.33–63.56 ± 0.33 L of absolute ethanol was obtained from 100 kg of starch. Simultaneous saccharification and fermentation of the native starch raw materials, especially without pre‐activation of starch, can simplify the process and improve the economic index in the alcohol‐distilling industry. © 2012 Society of Chemical Industry